Aspek Hukum Lahan Sawah Dilindungi dan Tata Ruang: Legal Aspects of Protected Rice Land and Spatial Planning - Firman Nur Robbi, Yogya; Sadino; Suartini (Universitas Muhammadiyah Bima, 2024)
This research discusses the regulation and process of resolving discrepancies in using Protected Rice Fields (LSD) by Indonesian laws and regulations. LSD has an important role in protecting strategic food resources and ensuring national food security. The purpose of this study is to examine the regulatory framework governing LSD and identify challenges in the resolution process, as well as present steps that can be taken to improve LSD management. This research uses a normative research approach with an analysis of applicable regulations and procedures related to LSD in Indonesia. The research results highlight the need for increased coordination between central and regional governments in determining and monitoring LSD, strict law enforcement, regular updating of LSD data, outreach to the community, providing incentives to farmers, and increasing investment in agricultural infrastructure. These steps are expected to increase the effectiveness of LSD management, which will ultimately support national food security and farmer welfare.